Electronic commerce patterns in Europe: Cluster analysis of online shopping intensity - Brcanov Dejan; Vučenović Sonja; Marić Dražen; Marić Radenko (Marketing (Beograd. 1991))
Electronic shopping represents a key segment of the digital economy, changing consumer habits and becoming a significant driver of economic development. The development of digital technologies and increased connectivity have contributed to the rapid growth of electronic commerce, but its intensity varies between countries, opening up space for analysis of the factors that shape these differences. This paper analyse electronic commerce in European countries through cluster analysis, grouping countries according to the frequency of online shopping in order to identify pat-terns and determinants of e-commerce development. The research covers countries from the territory of Europe, providing an insight into the various economic, technological and social characteristics of the region. The results showed the existence of four clusters, with significant differences in factors such as internet availability, information literacy, logistics infrastructure, educational level and differences between urban and rural areas. The identified differences illuminate regional disparities and provide a basis for understanding the dynamics of online shopping in Europe.